Extraction and Characterization of Zein Protein from Corn for Controlled Drug Release - Uan-on*, Tanat; Baibang, Chanattha; Shuwisitkul, Duangratana (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The aim of the present study was to analyze the effect of β-zein in a coating film and on the controlled drug release properties in pharmaceutical tablets. The zein protein was obtained by solvent extraction using acetic acid, ethanol and isopropanol with different concentrations from 70 to 90% v/v in each solvent. The structure of the extracted zein protein was analyzed using SDS-PAGE and FT-IR. Only the zein extracted using acetic acid had a low molecular weight (17 kDa), which was represented as β-zein. The extracted zein from 70% isopropanol and 70% acetic acid was then used to prepare coating solutions for coating tablets and compared with commercial zein. The film was coated on the tablets containing a model drug, namely theophylline or chlorpheniramine maleate, with the samples prepared using the wet granulation method. Investigation of the film elasticity indicated that the extracted zein from acetic acid had greater flexibility than the commercial zein. The dissolution profiles of the coated tablets from the extracted zeins were slower than that of the commercial zein as zero-order release profiles. The better elongation and flexibility could prevent penetration of the solvent into the core of the tablet and help retain the film function.